Kierunki analizy gospodarowania czynnikiem ludzkim w socjalistycznym przedsiębiorstwie leśnym - Van Nam, Nguyen (Wydział Prawa i Administracji UAM, 1974)
The author presents the existing system of recording employment, productivity of labour and wages. He states that the records are not sufficient for a thorough analysis of managing the human factor. He puts forward for consideration a change in the recording and analysis to examine if the wages are justifiable from the social point of view.